Psoriasis concurrent with inflammatory bowel disease. (25th October 2013) - Park, H.S.; Koh, S.J.; Park, G.Y.; Lee, D.H.; Yoon, H.S.; Youn, J.I.; Cho, S.
Abstract Background Previous studies have indicated an association between psoriasis and inflammatory bowel disease (IBD), and the concurrence of the two diseases reportedly has higher morbidities in Caucasian populations. However, reports on the concurrence of psoriasis with IBD in the Asian population in the literature are scarce. Objective To analyse the characteristics of psoriasis concurrent with IBD and investigate the associated morbidity in the Asian population. Methods We retrospectively examined the medical records of 15 patients with a confirmed diagnosis of both psoriasis and IBD. Sixty age‐, gender‐, and ethnicity‐matched patients with a confirmed diagnosis of only psoriasis were included as controls. Both cases and controls had visited the Seoul National University Hospital or Seoul National University Boramae Hospital between 1990 and 2012. The characteristics of psoriasis, presence of comorbidity and laboratory parameters were compared between the two groups. Results Compared to controls with psoriasis only, cases of psoriasis concurrent with IBD had a younger age of onset, longer duration of psoriasis and a higher Psoriasis Area Severity Index (PASI) score. A larger proportion of cases was treated with phototherapy, systemic therapy and biologics. However, all these differences above were not statistically significant. Cases of psoriasis with concurrent IBD showed higher erythrocyte sedimentation rate and C‐reactive protein levels compared with the controls (both P = 0.000). Furthermore, this case group had a higher proportion of patients with psoriatic arthritis and with more than one autoimmune disease as compared with the control group (P = 0.007 and 0.005 respectively). Conclusion Asian patients having psoriasis concurrent with IBD exhibited different characteristics as compared with those having psoriasis only, particularly in terms of psoriasis severity, risk of psoriatic arthritis, systemic inflammatory parameters and presence of autoimmune comorbidity. However, further studies elucidating the exact pathogenesis and including a larger number of patients are required.